Various exact wave solutions for KdV equation with time-variable coefficients - Ismael, Hajar F.; Murad, Muhammad Amin S.; Bulut, Hasan (Elsevier, 2022)
In this study, we investigate the (2 + 1)-dimensional Korteweg-De Vries (KdV) equation with the exten-sion of time-dependent coefficients. A symbolic computational method, the simplified Hirota's method, and a long-wave method are utilized to create various exact solutions to the suggested equation. The symbolic computational method is applied to create the Lump solutions and periodic lump waves. Hi-rota's method and a long-wave method are implemented to explore single-, double-and triple-M-lump waves, and interaction physical phenomena such as an interaction of single-M-lump with one-, two-soliton solutions, as well as a collision of double-M-lump with single-soliton waves. Furthermore, the simplified Hirota's method is employed to explore complex multi-soliton solutions. To realize dynamics, the gained solutions are drawn via utilizing different arbitrary variable coefficients.(c) 2021 Published by Elsevier B.V. on behalf of Shanghai Jiaotong University. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ )
Keywords: Hirota?s method; Lump solutions; Interaction phenomena; Complex multi-soliton waves; KdV equation